2014
DOI: 10.1681/asn.2013070734
|View full text |Cite
|
Sign up to set email alerts
|

Speckle Tracking Echocardiography Detects Uremic Cardiomyopathy Early and Predicts Cardiovascular Mortality in ESRD

Abstract: Cardiovascular mortality is high in ESRD, partly driven by sudden cardiac death and recurrent heart failure due to uremic cardiomyopathy. We investigated whether speckle-tracking echocardiography is superior to routine echocardiography in early detection of uremic cardiomyopathy in animal models and whether it predicts cardiovascular mortality in patients undergoing dialysis. Using speckle-tracking echocardiography in two rat models of uremic cardiomyopathy soon (4-6 weeks) after induction of kidney disease, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 67 publications
7
92
1
1
Order By: Relevance
“…Furthermore, no significant differences in GLS were observed when comparing CKD, dialysis, and transplanted patients. These findings are consistent with studies that showed less negative LV longitudinal strain in ESRD patients than in controls [10, 13, 24], but are at variance with a previous study that reported better GLS in ESRD patients on dialysis treatment than in those with CKD not requiring dialysis yet [25]. We have no reliable explanations of this discrepancy, since in both studies, volume status was similar in non-dialysis and dialysis patients, thus ruling out the occurrence of chronic fluid overload as the cause of worse GLS in the group of CKD patients not undergoing extracorporeal treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, no significant differences in GLS were observed when comparing CKD, dialysis, and transplanted patients. These findings are consistent with studies that showed less negative LV longitudinal strain in ESRD patients than in controls [10, 13, 24], but are at variance with a previous study that reported better GLS in ESRD patients on dialysis treatment than in those with CKD not requiring dialysis yet [25]. We have no reliable explanations of this discrepancy, since in both studies, volume status was similar in non-dialysis and dialysis patients, thus ruling out the occurrence of chronic fluid overload as the cause of worse GLS in the group of CKD patients not undergoing extracorporeal treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Abnormal GLS was independently associated with both all-cause and CV mortality also in patients with CKD and those undergoing hemodialysis (HD) [13, 14]. …”
Section: Introductionmentioning
confidence: 99%
“…The E-toe9 ratio is now a standard component of diastolic assessment (25) and particularly useful in differentiating normal from pseudonormal diastolic function. Additionally, recent studies have illustrated the prognostic utility of using speckle tracking echocardiography to quantify systolic function in patients with predialysis CKD (26) and ESRD (27,28). Thus, the less striking associations observed for EF could be interpreted as a limitation of the conventional evaluation of systolic function in patients with normal EF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in a cohort of 241 HD patients that an increase of 1 ms -1 of PWV is associated with an adjusted HR of 1.39 (95% CI 1.19-1.62) for all-cause mortality [21] . The recognition of GLS as an important prognostic risk factor has only recently emerged [4,5,16,22] . In 88 stable HD patients with a mean follow-up of 25 ± 9.9 months, Liu et al [4] reported that a less negative GLS (performed during dialysis) was associated with a 3.57 times higher all-cause mortality (95% CI 1.41-9.04, p = 0.01).…”
Section: Discussionmentioning
confidence: 99%